2012
DOI: 10.1111/j.1365-3164.2012.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal and serological testing for mites in healthy beagle dogs

Abstract: Our results suggest that dogs that have IDT reactions and positive serology are asymptomatically sensitized, while dogs that react at higher allergen concentrations, but have negative serology, do so as a result of irritant reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
8
1
1
Order By: Relevance
“…A previous study evaluating skin test reactivity of dust mites from two manufacturers found significant correlation and agreement when comparing batches of allergens from different manufacturers . Although the present study also had agreement with subjective scoring and objective measurements for D. farinae between manufacturers, significant differences in subjective scoring and objective measurements for Alternaria , cat dander and P. pretense were discovered between manufacturers.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A previous study evaluating skin test reactivity of dust mites from two manufacturers found significant correlation and agreement when comparing batches of allergens from different manufacturers . Although the present study also had agreement with subjective scoring and objective measurements for D. farinae between manufacturers, significant differences in subjective scoring and objective measurements for Alternaria , cat dander and P. pretense were discovered between manufacturers.…”
Section: Discussionsupporting
confidence: 65%
“…Before this can be done, it is necessary to determine the ITC for similar allergenic extracts from different manufacturers. With the exception of two previous studies evaluating the response to intradermal dust mite allergens from multiple manufacturers in clinically nonallergic dogs, there is a lack of ITC studies evaluating a variety of allergenic extracts from multiple manufacturers. For this reason, and the fact that the exact ITC for many allergens is unknown, further evaluation of ITCs is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be significant differences when allergens are considered separately. The tests described in the literature show that a high percent of healthy dogs (about 20%) present detectable titres of antibodies against at least one species of mites, especially against D. farine, although they are lower than those found in atopic dogs (Koebrich et al 2012). It must be pointed out, however, that the results of ELISA test should be assessed together with the presence of clinical symptoms of atopic dermatitis, the result itself being not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…De fato, estudos que avaliam a resposta dos cães ao desafio do alergênio epicutâneo demonstraram inflamação associada ao alérgeno apenas aos itens aos quais os pacientes já tinham IgE específica11 . No entanto, nem níveis de IgE totais nem alérgenos são consistentes para prever o desenvolvimento de doença clínica em pacientes sensibilizados12,13 . Esses achados demonstram a necessidade absoluta de incluir informações clínicas e história na interpretação de qualquer teste específico para alérgenos.…”
unclassified